1992
DOI: 10.2527/1992.7061677x
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical mastitis in ewes and its effect on lamb performance

Abstract: Two studies were conducted to 1) assess the effectiveness of the California mastitis test (CMT) relative to direct microscopic somatic cell count (DMSCC) and(or) somatic cell count (SCC) procedures for detecting subclinical mastitis in ewes, 2) determine the incidence of subclinical mastitis based on repeated or single sample measures and organisms associated with the inflammation, and 3) assess the relationship between milk quality measures and lamb performance. The relationship between DMSCC and SCC scores w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
10

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 0 publications
1
19
0
10
Order By: Relevance
“…On the other side, the most frequent pathogen isolated from subclinical cases in our study in spring was CNS (66.6 % of isolations) and, in summer, was S. aureus. CNS have been reported to be the major cause of non-clinical IMIs in a number of previous investigations (Beheshti et al 2010;Watson and Buswell 1984;Hueston et al 1986;Bor et al 1989;Keisler et al 1992;McDougall et al 2002;Batavani et al 2003). Comparison between the severity of SCM and pathogens showed that the S. aureus could intensify SCM.…”
Section: Fig 2 Bacterial Species Isolated From Subclinical Mastitis mentioning
confidence: 89%
“…On the other side, the most frequent pathogen isolated from subclinical cases in our study in spring was CNS (66.6 % of isolations) and, in summer, was S. aureus. CNS have been reported to be the major cause of non-clinical IMIs in a number of previous investigations (Beheshti et al 2010;Watson and Buswell 1984;Hueston et al 1986;Bor et al 1989;Keisler et al 1992;McDougall et al 2002;Batavani et al 2003). Comparison between the severity of SCM and pathogens showed that the S. aureus could intensify SCM.…”
Section: Fig 2 Bacterial Species Isolated From Subclinical Mastitis mentioning
confidence: 89%
“…Algumas pesquisas relatam que o CMT usado no campo para detectar infecções subclínicas em ovelhas é menos seguro e demonstram que a capacidade desse teste em predizer as infecções, depende da prevalência e dos agentes presentes no rebanho (Hueston et al 1986, Keisler et al 1992. Quanto à utilização, o CMT é considerado um teste subjetivo para ovinos, razão pela qual a padronização do teste é feita para o leite de bovino, pois o CMT é mais acurado nesta espécie (Green 1984, Maisi et al 1987.…”
Section: Discussionunclassified
“…A bactéria isolada com maior frequência nas amostras Keisler et al (1992), Fthenakis (1994), Stefanakis et al (1995) e Burriel (1997. O Staphylococcus coagulase negativo é considerado, por alguns autores, como patógeno secundário ou oportunista presente na microbiota da pele do teto dos animais.…”
Section: Discussionunclassified
“…A mastite também está associada com a performance dos cordeiros (Burris & Baugus 1955, Torre-Hernandez & Hohenboken 1979, Fthenakis & Jones 1990) descarte de ovelhas, mortes (Watson & Buswell 1984), custos com tratamentos (Keisler et al 1992), gastos adicionais com mão-de-obra (Larsgrad & Vaabenoe 1993) e alteração na composição do leite (Green 1984, Hueston et al 1986b.…”
Section: Introductionunclassified
“…Este processo inflamatório pode ser diagnosticado pela inspeção e palpação, e ainda por exames complementares que avaliem a celularidade do leite e o isolamento de agentes patogênicos (Keisler et al 1992).…”
Section: Introductionunclassified